Strengthening Student Literacy through Deep Learning-Based Indonesian Language Learning - Weti Yunaika (CV. Edujavare Publishing, 2026)
In the context of education, literacy is not limited to the ability to read and write, but also includes the capacity to understand, interpret, evaluate, and produce meaningful information in various forms. This study aims to analyze the strengthening of student literacy through deep learning-based Indonesian language learning. Literacy is an essential competence in modern education because it supports students’ abilities to understand, analyze, evaluate, and communicate information effectively in academic and social contexts. The study employed a literature review method by examining various books, journal articles, and educational documents related to literacy, deep learning, and Indonesian language instruction. The findings indicate that Indonesian language learning has a strategic role in developing students’ literacy competencies through reading, writing, speaking, and listening activities. The implementation of deep learning approaches encourages meaningful learning experiences by promoting critical thinking, collaboration, reflection, creativity, and active student participation. In addition, deep learning-based instruction contributes to the development of digital literacy and higher-order thinking skills that are relevant to twenty-first-century educational demands. Although several challenges remain, such as conventional teaching methods and limited educational resources, the integration of deep learning principles into Indonesian language learning can create more interactive, contextual, and transformative literacy learning experiences. Therefore, deep learning-based Indonesian language learning is considered an effective strategy for strengthening student literacy and improving the overall quality of education.